Ekstraksi dan Analisis Produk di Marketplace Secara Otomatis dengan Memanfaatkan Teknologi Web Crawling - Ivan Nathaniel Husada; Edward Hanafi Fernando; Hetthroh Sagala; Ariel Elbert Budiman; Hapnes Toba (Maranatha University Press, 2019)
Along with the advancement in technology, todays community begins to abandon conventional shopping methods where buyers must come to the seller's shop. Nowadays community mostly doing online shopping because the process is considered more convenience. Because of this, there are more and more online marketplace users. Much more data can be retrieved with the increasing number of online marketplace users. Because of the large amount of data the process for extracting the data so that it can be seen and utilized becomes possible. The purpose of this journal is to show data and extraction method from an online marketplace system so that the results can be visualized and users can analyze the data. The data extraction method that will be used is the web crawling method and web scraping where after the data is successfully extracted and cleaned it will be visualized with the power BI application. The experiments show that the method is useful to conduct analysis.